The Influence of Financial Behavior on the Decision to Use Sharia Crowdfunding as Access to Capital for Micro, Small and Medium Enterprises - Delya Dwiyanti (Universitas Mercu Buana, 2022)
This study aims to determine the effect of awareness, trust and risk perception on the decision to use sharia crowdfunding. The subject of this research is Micro, Small and Medium Enterprises (MSMEs) located in West Jakarta. This research is a quantitative type that uses primary data. The sample used in this study were 130 MSME respondents. The sampling method was carried out by the purposive sampling method. This study uses logistic regression data analysis techniques to analyze the decisions of Micro, Small and Medium Enterprises (MSMEs) using sharia crowdfunding using IBM Statistic SPSS 25 software. In general, the results of this study indicate that awareness has a positive and significant effect on decisions to use sharia crowdfunding, trust Positive and Significant influence on the Decision to Use Sharia Crowdfunding, Risk Perception has a Positive but Not Significant effect on the Decision to Use Sharia Crowdfunding. Keywords— Awareness, Trust, Risk Perception, Decision to Use, Sharia Crowdfunding